Methotrexate - Nilgün Şentürk (Turkderm Turkish Archives of Dermatology and Venereology, 2022)
Methotrexate is a drug used in the treatment of psoriasis and psoriatic arthritis. It shows its effect by binding to dihydrofolate reductase, reducing purine synthesis and cell proliferation. When used as a monotherapy, methotrexate shows its effect late and achieves a 50-75% recovery in skin lesions. Patients using methotrexate should periodically be monitored for toxicity with relevant laboratory parameters. Its use in combination with folic acid reduces the risk of toxicity. Using it in combination with cyclosporine in low doses may lower the toxicity risk of both. Its use in combination with phototherapy and acitretin has been found considerably effective.